COMPARISON OF EFFECTS OF ENALAPRIL AND UNCONTROLLED ANTIHYPERTENSIVE THERAPY ON INSULIN RESISTANCE, ENDOTHELIUM FUNCTION, MARKERS OF INFLAMMATION AND PLATELET ACTIVITY IN PATIENTS WITH METABOLIC SYNDROME - M. N. Mamedov; T. V. Ektova; O. A. Litinskaya; T. Sh. Dzhakhangirov; O. V. Kosmatova (Столичная издательская компания, 2016)
Aim. To assess influence of enalapril and uncontrolled antihypertensive therapy on insulin resistance, endothelium function, markers of inflammation, and platelet activity in patients with metabolic syndrome (MS). Material and methods. 41 patients with MS (21 women and 20 men, aged 58±2 years) were included into open parallel controlled study. MS was defined according to III report of USA Educational Program on cholesterol (2001). Patients were divided into 2 groups. Patients of the 1st group received enalapril (Enam, Dr. Reddy's) 10 mg daily with further dose titration to 20 mg daily. Patients of the  2nd group continued receiving the same antihypertensive therapy as before (15% - inhibitors of angiotensin converting enzymes, 15% - в-blockers, 15% - diuretics, and 20% of patients - combined therapy). Study duration was 12 weeks. Results. Therapy with enalapril during 3 months resulted into significant decrease in systolic and diastolic blood pressure (BP) by 13 and 9% respectively. BP level decreased insignificantly (by 4,5 and 2% respectively) in controlled group. Ratio of plasma concentration of glucose to insulin in the 1st group increased by 14% before glucose load, and by 25% (p<0,05) 2 hours after peroral glucose load, while in the 2nd group decrease in these figures was noted by 12 and 5% respectively. This shows that treatment with enalapril, unlike uncontrolled antihypertensive therapy, lead to decrease in insulin resistance. Cuff test revealed significant increase in growth of brachial artery diameter in the group of patients, who received enalapril (12% before treatment, and 17% after treatment). Regular antihypertensive therapy didn't change this parameter significantly (13 and 13,8% respectively). C-reactive protein level decreased by 48% (p<0,05) in the 1st group. Insignificant increase of this marker's level was observed in the 2nd group. Platelet functional activity in both groups didn't change significantly. Conclusion.  Together with strong antihypertensive effect, enalapril monotherapy is more efficient than regular antihypertensive therapy in reducing insulin resistance and chronic subclinical inflammation, as well as it has priority in improving endothelium depending vasodilatation.